The environmental effects of effluent disposal at gold mines in Zimbabwe: a case study of Tiger Reef Mine in Kwekwe - Jerie, Steven; Sibanda, Edmore (Clarion University of Pennsylvania, 2016)
This study examines the environmental effects of effluent disposal at gold mines in Zimbabwe with particular reference to Tiger Reef Gold Mine in the Kwekwe district. The methods of data collection included questionnaire surveys and interviews directed at key informants to solicit information on the environmental impacts of the environment and human health. Field tests and observations were also undertaken on parameters, such as cyanide and mercury concentrations, and these were compared with the recommended standards of the World Health Organization (WHO) and the Standards Association of Zimbabwe (SAZ). The conclusions drawn from the study are that waste water management practices at Tiger Reef Mine are associated with negative impacts on the environment as well as human health. There is also lack of monitoring and enforcement of the relevant environmental management legislation by the relevant authorities in the country in order to control the negative impacts. It is recommended that the mine needs to adopt a holistic approach in waste effluent water treatment by using strategies, such as closed circuit treatment, microbial activities, and cyanide bio-degradation.